Using cost-benefit analysis in developed and developing countries : is it the same? - Quah, Euston (Monetary Authority of Singapore, 2022)
Nobel laureate and economist Simon Kuznets put forth the concept of gross domestic product (GDP) in response to a need for good data in public policy planning in the 1930s. Since then, policymakers have increasingly relied upon GDP and other national income indicators. If only one macro indicator is available in any given country, chances are the indicator is the country’s GDP. However, as Kuznets himself and other critics of GDP have pointed out, national income statistics are not ideal measures of welfare (Kuznets, 1934). Of the many criticisms, two of the more prominent are the lack of consideration of equity and the fact that these statistics only measure economic activity and do not account for non-economic costs of growth (Kuznets, 1962).